2008
DOI: 10.1088/0022-3727/42/2/025205
|View full text |Cite
|
Sign up to set email alerts
|

PIC simulations of the separate control of ion flux and energy in CCRF discharges via the electrical asymmetry effect

Abstract: Recently a novel approach for achieving separate control of ion flux and energy in capacitively coupled radio frequency (CCRF) discharges based on the electrical asymmetry effect (EAE) was proposed (Heil et al 2008 J. Phys. D: Appl. Phys. 41 165202). If the applied, temporally symmetric voltage waveform contains an even harmonic of the fundamental frequency, the sheaths in front of the two electrodes are necessarily asymmetric. A dc self-bias develops and is a function of the phase angle between the driving vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
259
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(277 citation statements)
references
References 56 publications
15
259
3
Order By: Relevance
“…4 It is possible, however, to control the ion energy using well-separated multiple frequencies or through frequency coupling of harmonics, for example, via the electrical asymmetry effect (EAE), independently of other plasma parameters and, in particular, independently of the ion flux. [5][6][7][8][9][10][11][12][13][14][15][16] In this paper, we will investigate the effect of both amplitude asymmetric and slope asymmetric waveforms on ion properties in CF 4 plasmas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 It is possible, however, to control the ion energy using well-separated multiple frequencies or through frequency coupling of harmonics, for example, via the electrical asymmetry effect (EAE), independently of other plasma parameters and, in particular, independently of the ion flux. [5][6][7][8][9][10][11][12][13][14][15][16] In this paper, we will investigate the effect of both amplitude asymmetric and slope asymmetric waveforms on ion properties in CF 4 plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…According to an analytical model developed by Czarnetzki et al, the appearance of a self-bias, g, [5][6][7] due to the EAE, can be expressed as g ¼ÀṼ m1 þ eṼ m2 1 þ e ;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,15,16,18,20 The Fourier spectrum of the electron current density of the 54. 24 MHz discharge again reveals the alternating amplitudes for odd and even …”
Section: -mentioning
confidence: 94%
“…Another way of inducing an asymmetry is via the Electrical Asymmetry Effect (EAE), [17][18][19][20][21][22][23][24][25][26] i.e., by using a driving voltage waveform with unequal absolute values of the global maximum and minimum. Donko et al 17 have shown that the PSR is self-excited in geometrically symmetric, electrically asymmetric discharges operated at a fundamental frequency (13.56 MHz) and its second harmonic (27.12 MHz).…”
Section: Introductionmentioning
confidence: 99%